Room-Temperature Synthesis of a Hollow Microporous Organic Polymer Bearing Activated Alkyne IR Probes for Nonradical Thiol-yne Click-Based Post-Functionalization - Park, Jong In; Jang, June Young; Ko, Yoon Joo; Lee, Sang Moon; Kim, Hae Jin; Jang, Hye Young; Ko, Kyoung Chul; Son, Seung Uk (Chemistry - An Asian Journal, 2021)
This work shows that hollow microporous organic polymer (H-MOP-A) with activated internal alkynes as IR probes can be prepared by template synthesis based on acyl Sonogashira-Hagihara coupling at room temperature. The H-MOP-A is a versatile platform in the main chain PSM based on nonradical thiol-yne click reaction. Moreover, an IR peak of internal alkynes in the H-MOP-A is very intense and could be utilized in the monitoring of thiol-yne click-based main chain PSM. The functionalized H-MOP-A with carboxylic acids (H-MOP-CA) showed efficient adsorption toward Ag+ ions. The resultant H-MOP-CA-Ag showed excellent performance in the CO2 fixation to α-alkylidene cyclic compounds.
Keywords: Activated alkynes; Click reaction; Cyclic compounds; Internal alkynes; Microporous organic polymers; Post-functionalization; Room temperature synthesis; Template synthesis; Acyl Sonogashira coupling; Carbon dioxide conversion; Microporous organic polymer; Post-synthetic modification; Thiol-yne click reaction